PTU-228 Predicting difficult colonoscopy using the St Mark's difficult colonoscopy scoring system: a pilot study. (28th May 2012) - Nakamura, M; Murino, A; Despott, E; Suzuki, N; Bourikas, L; Man, R; Fraser, C
Abstract : Introduction: Colonoscopy can sometimes be difficult. This may be due to a number of factors such as age, gender, increased colon length, waist/hip ratio <1, BMI<22, abdominopelvic surgery and a history of constipation. Colonoscopists tend to develop their own strategies based on their personal experience and the availability of specialised equipment. A scoring system based on these factors could be a useful predictor of difficult colonoscopy with the advantage that such a score could be calculated prior to the procedure. We therefore developed an evidence based difficult colonoscopy score (DCS), incorporating factors associated with difficult colonoscopy. The aim of this study was to validate the reliability of the proposed St Mark's DCS evaluating the relationship between each factor and caecal incubation time. Methods: Patients referred for routine colonoscopy were recruited. 30 patients were prospectively selected. Each patient was screened using a questionnaire. Colonoscopies were started with an adult colonoscope, but if needed, alternative options such as a paediatric colonoscope or real time magnetic imager were made available on request. Results: The overall caecal incubation rate was 97% (29/30). One patient was excluded due to a colonic stricture. The median DCS was 3 (range 0–6). Median insertion time was 8 min (range 3–23). In three patients colonoscopists changed to an alternative option during colonoscopy. There was a significant correlation between the DCS and insertion time (r=0.511, p=0.005, Pearson's correlation coefficient). Moreover, if the DCS was five or more, caecal intubation time was >15 min suggesting a strong correlation. The significant factors by univariate analysis influencing a caecal intubation time of more than 15 min were "Waist/hip ratio <1 and/or BMI<22", "over 60 years old" and "Constipation". Multivariate analysis suggested the most significant factor for difficult colonoscopy was a history of constipation. Conclusion: This pilot study has shown the DCS could be a useful tool for the prediction of difficult colonoscopy. This could be of benefit when scheduling lists for training and choosing the level of experience of colonoscopists before procedures are performed. A large study is planned. Competing interests: None declared.